Pengolahan Sampah Organik Untuk Ekoenzim dan Budidaya Maggot di Desa Tlogojati, Dusun Windusari, Kabupaten Wonosobo - Bagas Putra Satria; Nasywa Arifah; Reza Amelia Putri; Animna Rahma Zain; Kholfiana Afriani; Niken Rizqi Amborowati; Randika Hadi Putra; Bagawati Nopayulita; Wasesa Wardini; Deka Ridho Rizkiyani (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The issue of organic waste in Tlogojati Village, Windusari Hamlet, Wonosobo Regency has been increasing due to the lack of public awareness regarding its management. This community service program aims to provide education and hands-on practice in organic waste processing through the production of eco-enzymes and maggot cultivation. The methods used include socialization, practical training, and participatory mentoring. The program results indicate an improvement in the community’s understanding and skills in processing organic waste into valuable products. Residents have begun producing eco-enzymes as natural cleaners and organic fertilizers, as well as implementing maggot cultivation as an alternative solution for organic waste management and animal feed. The impact of this program extends beyond environmental awareness, as it also creates economic opportunities for the local community. With the support of the village government and active community participation, a sustainable waste management system can be developed in Tlogojati Village.